Kant and Nāgārjuna: A hermeneutic inquiry into transcendental aesthetics - Kumara, J. D. A. (Journal of Multidisciplinary and Translational Research (JMTR), 2024)
The Madhyamaka tradition of Buddhism, with development of śūnyatā philosophy, was widely considered as founded by Nāgārjuna (ca 150–250 CE) who is best known as one of most important philosophers in the history of Buddhism. Critics do not generally regard Nāgārjuna’s philosophy of emptiness, Madhyamaka, as a theory of nonexistence or nihilism. Its acceptance of absolute non-being leads to recognition of a hyperousiological (hyper-Being that mystically surpasses Being) ontotheological superbeing, which is a priori and that it has similarities with transcendental aesthetics where Kant deals with nature of sensibility. Hyperousiology denotes a "Being beyond being" and predominantly used in negative theology. Negative theology is heavily relied on “denegations” that lead to a hyper-theology affirming God as hyperousious, as defined by Pseudo-Dionysius, knowing God by unknowing or “denominating” God. Such mystical theology is a “theology of absence”, a higher apophasis that overcomes both affirmation and negation to sustain a hyperessence. Kant’s transcendental aesthetics is considered as the investigation of a priori elements which enter into Perception. Kant toiled hard to understand human cognition and human judgment; his focus was on innate human capability of making judgments by a cognitive faculty. Kant claims the matter of all appearance is only given to us a posteriori, but its form must all lie ready for it in the mind a priori and can therefore be considered separately from all sensation. The foundational idea of Madhyamaka school, śūnyatā, the set of ultimately existent things, is an empty set that transcends epistemic foundations in linguistic and conceptual conventions. Accordingly, Madhyamaka school has a two-truth doctrine: ultimate truth (paramārtha-satya) and relative truth (saṃvṛti-satya). Like a priori sensibility, it is argued, ultimate truth (paramārtha-satya) is separate from all sensation as it transcends conceptual conventions. The major research problem investigated in this study is whether the ultimate truth (paramārtha-satya) of Madhyamaka school acts as a priori sensibility and creates a synthesis with relative truth (saṃvṛti-satya) making cognition transcendentally ideal and empirically real? This inquiry delves into investigating interconnections between transcendental ideals and empirical reals. Hermeneutics has been employed as the principal research method to interpret both Kant and Nāgārjuna on aesthetic judgment.
Keywords: Kant; Nāgārjuna; Transcendental Aesthetics; Madhyamaka Buddhism; Śūnyatā Philosophy